Ethical Analysis of the Application of Assisted Reproduction Technologies in Biodiversity Conservation and the Case of White Rhinoceros (Ceratotherium simum) Ovum Pick-Up Procedures - Biasetti, Pierfrancesco; Hildebrandt, Thomas B.; Göritz, Frank; Hermes, Robert; Holtze, Susanne; Galli, Cesare; Lazzari, Giovanna; Colleoni, Silvia; Pollastri, Ilaria; Spiriti, Maria Michela; Stejskal, Jan; Seet, Steven; et al. (Frontiers in Veterinary Science, 2022)
Originally applied on domestic and lab animals, assisted reproduction technologies (ART) have also found application in conservation breeding programs, where they can make the genetic management of populations more efficient, and increase the number of individuals per generation. However, their application to wildlife conservation opens up new ethical scenarios that have not yet been fully explored. This paper presents a frame for the ethical analysis of the application of ART procedures in conservation based on the Ethical Matrix, and discusses a specific case study – ovum-pick up procedures performed in the current conservation efforts for the northern white rhinoceros (Ceratotherium simum cottoni) – providing a template for the assessment of ART procedures in further projects involving other endangered species.